How Liquidity, Leverage, and Business Growth Affected the Financial Crisis and Its Impact on Company Value? - Palupi, Rini (Sekolah Menengah Kejuruan (SMK) Pustek, 2023)
The company's growth is highly expected by internal and external parties of the company, because good growth signals the development of the company. This study aims to determine the effect of Liquidity, Leverage and Firm Growth on Financial Distress and its Implications for Company Value in food and beverage companies listed on the Indonesia Stock Exchange in 2015-2021. This type of research uses associative quantitative methods. The population in this study amounted to 54 companies, the selection of sample techniques in this study used the purposive sampling method, then the samples used in this study were 11 companies. The data used in this study are secondary data. Panel data regression testing using chow test, hausman test and langrange multiplier test. Data processing techniques using the E-views 12 program, namely using descriptive statistical tests, selection of panel data regression models, classical assumption tests, panel data regression analysis, hypothesis tests, determination coefficient tests, path analysis and sobel tests. The results of this study show that, simultaneously, liquidity (current ratio), leverage (debt to equity ratio) and firm growth together have a significant effect on financial distress.